Beginning and intermediate algebra - Miller, Julie 1962- (Higher Education, 2006)
Miller/O'Neill's Beginning and Intermediate Algebra is an insightful textbook written by instructors who have first-hand experience with students of developmental mathematics. Through specially designed exercise sets, student-friendly writing, carefully organized page-layout, and helpful hints and tips, Beginning and Intermediate Algebra engages students in their study of mathematics and paves the pathway for success.